Referral and treatment pathways for pseudomyxoma peritonei of appendiceal origin within a national treatment programme. (26th July 2018) - Fish, R.; Renehan, A. G.; Punnett, G.; Aziz, O.; Fulford, P.; Selvasekar, C.; Wilson, M.; Halstead, R.; O'Dwyer, S. T.
Abstract: Aim: Pseudomyxoma peritonei (PMP) is a rare neoplasm of the appendix, which if untreated disseminates throughout the abdominal cavity and generates considerable morbidity. Since 2002 in the UK, patients with PMP have been managed via two nationally commissioned centres. We evaluated referrals and treatment pathways over time at the Manchester centre. Method: Data from all patients referred with suspected PMP were prospectively collected (2002–2015). Definitive treatment was cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy. Disease burden was quantified using the Peritoneal Cancer Index (PCI) (score 0–39) and complete cytoreduction (CC) defined by scores of 0/1. Novel treatment algorithms were developed for patients with low grade appendiceal mucinous neoplasm (LAMN) localized to the peri‐appendiceal tissue. Results: In all, 817 patients with confirmed PMP were referred increasing from 11 in 2002 to 103 in 2015. Disease burden was high with a mean PCI of 31 in the first quartile (Q1), levelling off to 15, 15, 17 thereafter ( P  =   0.002). The proportion of CC0/1 increased from 67% in Q1 to 77% Q2 and 74% Q3/4. Where complete cytoreduction was achieved, 5‐ and 10‐year overall survival was 77% and 66%. The proportion of patients referred with localized LAMN increased over time reaching 25% each year since 2010 ( P trend  < 0.0001). Two‐thirds of localized LAMN now undergo laparoscopically assisted risk‐reducing CRS. Conclusion: The establishment of a national treatment centre was associated with an initial presentation of patients with advanced disease. The programme has demonstrated a clear trend over time towards earlier referral and adoption of minimally invasive techniques for localized disease.